Highway Engineering. - Rogers, Martin (Wiley, 2016)
The repair, renovation and replacement of highway infrastructure, along with the provision of new highways, is a core element of civil engineering, so this book covers basic theory and practice in sufficient depth to provide a solid grounding to students of civil engineering and trainee practitioners. -Moves in a logical sequence from the planning and economic justification for a highway, through the geometric design and traffic analysis of highway links and intersections, to the design and maintenance of both flexible and rigid pavements -Covers geometric alignment of highways, junction and pavement design, structural design and pavement maintenance -Includes detailed discussions of traffic analysis and the economic appraisal of projects -Makes frequent reference to the Department of Transport's Design Manual for Roads and Bridges -Places the provision of roads and motorways in context by introducing the economic, political, social and administrative dimensions of the subject.